SRTR Program‐Specific Reports on Outcomes: A Guide for the New Reader - Dickinson, D. M.; Arrington, C. J.; Fant, G.; Levine, G. N.; Schaubel, D. E.; Pruett, T. L.; Roberts, M. S.; Wolfe, R. A. (American journal of transplantation, 2008)
Differences in outcomes indeed exist among transplant programs and organ procurement organizations (OPO). A growing set of tools are available from the Scientific Registry of Transplant Recipients (SRTR) to measure and assess these outcomes in the different phases of the transplant process. These tools are not intended to compare two individual programs, rather to help identify programs whose practices may need further scrutiny, to be either avoided, corrected or emulated. To understand which differences in outcomes might be due to underlying differences in populations served and which might be due to differences in treatment, it is important to compare outcomes to ‘risk‐adjusted’ expected values. Further, it is important to recognize and assess the role that random chance may play in these outcomes by considering the p‐value or confidence interval of each estimate. We present the reader with a basic explanation of these tools and their interpretation in the context of reading the SRTR Program‐Specific Reports. We describe the intended audience of these reports, including patients, monitoring and process improvement bodies, payers and others such as the media. Use of these statistics in a way that reflects a basic understanding of these concepts and their limitations is beneficial for all audiences.